(untitled) (Journal of actual problems of jurisprudence, 2019)
The study raises questions that contain the problematic side of the system of penal measures, foreseeing the analysis of the concepts of measures under criminal law and criminal law measures the impact, proposed his own concept of criminal law measures of exposure. Keywords: Penal Code; the system of criminal justice measures; to punish; measures of criminal law.